Circ-SHPRH in human cancers: a systematic review and meta-analysis - Xiong, Hong; Huang, Gaozhen; Zhu, Yi; Chen, Ruiqi; Zuo, Ling; Liu, Hongwei (Frontiers in Cell and Developmental Biology, 2023)
Circular RNA (circRNA) molecules are noncoding RNAs with ring-like structures formed by covalent bonds and are characterized by no 5′caps or 3′polyadenylated tails. Increasing evidence shows that circRNAs may play an important role in tumorigenesis and cancer metastasis. Circ-SHPRH originates from exons 26–29 of the SHPRH gene, and it is closely associated with human cancers. We searched PubMed, Web of Science, and Embase databases for relevant literatures until 24 December 2022. Eighteen research papers were included in this review, and 11 papers were selected for meta-analysis after screening. Three eligible published studies about circ-SHPRH were enrolled based on their tumor diagnosis aspect, 7 eligible published studies were related to overall survival (OS), and 3 eligible published studies were related to tumor grade. Many studies have shown that circ-SHPRH acts as a miRNA sponge or encodes a protein to regulate downstream genes or signal pathways, and exerts specific biological functions that affect the proliferation, invasion, and apoptosis of cancer cells. Meta-analysis showed that patients with high expression of circ-SHPRH had better OS (HR = 0.53, 95% CI 0.38–0.74, p-value <0.05) and lower TNM stage (HR = 0.33, 95% CI 0.18–0.62, p-value = 0.001). In addition, circ-SHPRH has potential diagnostic value (AUC = 0.8357). This review will help enrich our understanding of the role and mechanism of circ-SHPRH in human cancers. Circ-SHPRH has the potential to be a novel diagnostic and prognostic biomarker for various solid cancers.